2016
DOI: 10.4314/wsa.v41i2.07
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable and equitable sanitation in informal settlements of Cape Town: a common vision?

Abstract: Sustainability and equity are two desirable but ambiguous concepts often used to describe goals for sanitation services internationally and in South Africa. Both concepts are mentioned repeatedly in policy documents and government reports. There is, however, a gap between policy and implementation, and part of the problem lies in the challenge of reconciling the pressure to deliver immediate results with a long-term vision to strive towards sustainable and equitable sanitation services. Perspectives, prioritie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…It has to be noted that data on anemia presented in this analysis have to be interpreted with caution, bearing in mind that the South African population is battling both infectious diseases (e.g., TB and HIV) and NCDs (e.g., hypertension and diabetes). Moreover, despite the fact that malaria is not common in the country, individuals residing in rural and informal urban communities are exposed to various parasites (including nematodes) owing to their lack of access to decent sanitary services (flushing toilets, in particular) . Investigating the aforementioned challenges is beyond the scope of the current research; however, when we closely examined participants who had valid data on serum glucose, BP, and CRP levels, we observed that 2675 (84.0%), 767 (27.5%), and 1844 (63.1%) had CRP detected in their blood, abnormal HbAlc levels (i.e., had uncontrolled blood glucose levels), and DBP and SBP values that were above normal (i.e., were pre‐ and hypertensive), respectively (data not shown).…”
Section: Resultsmentioning
confidence: 84%
“…It has to be noted that data on anemia presented in this analysis have to be interpreted with caution, bearing in mind that the South African population is battling both infectious diseases (e.g., TB and HIV) and NCDs (e.g., hypertension and diabetes). Moreover, despite the fact that malaria is not common in the country, individuals residing in rural and informal urban communities are exposed to various parasites (including nematodes) owing to their lack of access to decent sanitary services (flushing toilets, in particular) . Investigating the aforementioned challenges is beyond the scope of the current research; however, when we closely examined participants who had valid data on serum glucose, BP, and CRP levels, we observed that 2675 (84.0%), 767 (27.5%), and 1844 (63.1%) had CRP detected in their blood, abnormal HbAlc levels (i.e., had uncontrolled blood glucose levels), and DBP and SBP values that were above normal (i.e., were pre‐ and hypertensive), respectively (data not shown).…”
Section: Resultsmentioning
confidence: 84%
“…Government policy might specifically limit the provision of sanitation infrastructure to interim solutions, such as periodic waste collection and chemical toilets (usually Ventilated Improved Pits) [42]. Such limitations might result from tensions between a responsibility to service what might be regarded as informal settlements, a need to discourage their growth, and a belief that they are temporary housing solutions until residents are relocated into housing projects or the settlements are upgraded to become "formalised" [8]. Lack of space or distance from bulk water infrastructure or wastewater treatment plants might prevent centralised, sewerage systems.…”
Section: Discussion and Concluding Remarksmentioning
confidence: 99%
“…Lack of space or distance from bulk water infrastructure or wastewater treatment plants might prevent centralised, sewerage systems. Local soil and hydrological regimes, e.g., high watertable, might lead to ground or surface water pollution by dense onsite greywater dispersal systems [1,4,8]. Thus, hybrid approaches involving government, NGOs and communities working together are most likely to produce sustainable sanitation solutions, which are likely to rely on decentralised systems.…”
Section: Discussion and Concluding Remarksmentioning
confidence: 99%
See 1 more Smart Citation
“…While all residents should be encouraged to use water responsibly, it is important to ensure that the burden of conserving water does not disproportionately affect indigent households and that the government continues to prioritise improvement of the level of services in underserved households living in informal settlements or backyard shacks. Thus, water and sanitation interventions in modern South Africa need to embed equity as a critical principle for building sustainable systems (Pan, Armitage, and Van Ryneveld 2015). The City critically did not reduce basic services to informal settlements or backyard dwellers during the water crisis (albeit people are typically limited by what they can carry from communal taps).…”
Section: Use: Behaviour and Equitymentioning
confidence: 99%